Pollution and contamination level of Cu, Cd, and Hg heavy metals in soil and food crop - Ramlan; M. Basir-Cyio; M. Napitupulu; T. Inoue; A. Anshary; Mahfudz; Isrun; M. Rusydi; Golar; Sulbadana; R. Bakri (International Journal of Environmental Science and Technology, 2022)
We aimed to assess and observe the accumulation of Cu, Cd, and Hg heavy metals on land and the contamination of plant tissues in Grand Forest Park, Palu, Indonesia, and its surrounding areas. The method used was a mix between survey and investigation, integrating data on research findings from before 2013 to 2016 with data from 2018. The data were analyzed using a correlation test, and descriptive statistics are presented in the form of tables and graphs. The results show that the highest concentration of Hg was found in the Poboya processing area (575.16 ppm) in 2013, though it gradually decreased to 287.64 ppm in 2018. The results of the Spearman’s rank test at the ∝ 0.05 level between average Cu land and Cu plant concentrations show that the obtained value ( r ) was 0.52 with a rho (ρ) of 0.13, which is not significant ( ρ 0.13 > 0.05), while for Cd and Hg metals, the obtained r values were 0.88 and 0.86, respectively. These two metals showed significant correlations between concentrations of Cd and Hg on land and Cd and Hg in plant tissues (both ρ 0.001 < 0.05). Specifically, the transfer factor (TF) value at the sampling sites of the Grand Forest Park area, Ngatabaru, and PBY from the average of various Hg concentrations in plants was much higher than the TF values of Cu and Cd, specifically being Hg > Cd = Cu or 0.61 > 0.17 = 0.17.